Analysing media effects: The third-person effect on party members - Idid, Syed Arabi; Mohamed, Shafizan (Penerbit Universiti Sains Malaysia, 2006)
This chapter discusses some selected communication theories and their relationship to several studies on what media can and cannot do on the audience. Special focus is given on Davison's Third-Person Effect theory (1996) and how it could be applied on the political communication studies. A study was conducted on Malaysian registered voters in 2004. The result showed that the respondents believed that the mainstream media that included newspaper and television were more influential on government supporters rather than on the opposition supporters and the non-patisan respondents.